Do Herbal Medicines Promote Weight loss? (https://doi.org/10.1111/dom.13973) (Diabetes, Obesity and Metabolism Now, 2023)
Aims The Risk Assessment and Management Programme-Diabetes Mellitus (RAMP-DM) is a multidisciplinary, protocol-driven, risk-stratified care model integrated into public primary care in Hong Kong for patients with type 2 diabetes mellitus (T2DM). This study evaluated the real-world 10-year cost-effectiveness of RAMP-DM from the public healthcare provider perspective. Materials and methods Programme costs from 2009 to 2019 were estimated using costing questionnaires and reported in 2019 US dollars. Direct medical costs were compared between patients enrolled in RAMP-DM and a propensity-score matched cohort receiving usual care only. Effectiveness was based on previously published 10-year estimates of absolute risk reduction in complications and all-cause mortality. The primary outcome was the incremental total direct medical cost per diabetes-related complication avoided over 10 years. Secondary outcomes included incremental cost per all-cause mortality avoided and programme cost per complication avoided. Sensitivity analyses examined the effects of parameter uncertainty and discounting. Results A total of 36 746 patients (18 373 in each group) were included. RAMP-DM was associated with absolute risk reductions of 12.1% for any complications and 16.2% for all-cause mortality. Accounting for the programme cost of US$329 per participant, total undiscounted direct medical costs over 10 years was US$10 543 lower per person among RAMP-DM participants (RAMP-DM: $23 430; usual care: US$33 973). RAMP-DM was a cost-saving strategy relative to usual care. Conclusions RAMP-DM was associated with better 10-year clinical outcomes and lower direct medical costs. These findings support the economic value of structured multidisciplinary diabetes management programmes in publicly funded primary care settings, although residual confounding and uncertainty in cost estimates should be considered.